2022
DOI: 10.1021/acs.chemmater.2c00694
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Assisted Anisotropic Chemical Etching of MoSe2 for Enhanced Phototransistors

Abstract: The etching process can serve as an effective top-down approach that facilitates direct construction of tuned patterns, reversely studying growth mechanisms and further inducing unexpected physical properties. Currently, etching behaviors of monolayer transition-metal dichalcogenides (TMDs) have been rarely explored and the intrinsic etching mechanism still needs to be fully elucidated. Here, we demonstrate a facile and controllable oxygen-assisted anisotropic chemical etching of two-dimensional (2D) materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…743 Besides aforementioned substrate modifications, it has been recently shown that O 2 plasma pretreatment of Si or Si/SiO 2 substrates prior to CVD growth of TMD monolayers results in in situ etching of such layers during CVD processes. Zhang et al 755 found that by adjusting O 2 plasma pretreatment time and CVD parameters, it was possible to generate well-defined etch patterns with zigzag-terminated edges inside CVD-grown TMDs. The O 2 plasma pretreatment of the substrate substantially promoted the etching without altering the chemistry of TMD layers, such as by oxygen doping or oxidation.…”
Section: Engineering Of Surface Energymentioning
confidence: 99%
“…743 Besides aforementioned substrate modifications, it has been recently shown that O 2 plasma pretreatment of Si or Si/SiO 2 substrates prior to CVD growth of TMD monolayers results in in situ etching of such layers during CVD processes. Zhang et al 755 found that by adjusting O 2 plasma pretreatment time and CVD parameters, it was possible to generate well-defined etch patterns with zigzag-terminated edges inside CVD-grown TMDs. The O 2 plasma pretreatment of the substrate substantially promoted the etching without altering the chemistry of TMD layers, such as by oxygen doping or oxidation.…”
Section: Engineering Of Surface Energymentioning
confidence: 99%
“…55 Consequently, the pursuit of morphology engineering through etching has garnered significant attention. 6,37,56,57 Notably, previous studies on the etching of 2D materials have been primarily limited to individual materials, with experimental investigations focusing on single cases and etching modes. Exploration of 2D heterostructures through etching is still in its nascent stages.…”
Section: Multi-stage Etched Graphene/hbn Heterostructuresmentioning
confidence: 99%
“…55 Consequently, the pursuit of morphology engineering through etching has garnered significant attention. 6,37,56,57…”
Section: Morphology Engineeringmentioning
confidence: 99%
See 2 more Smart Citations